Sexual Harassment Experiences among Visually Impaired Male Adults Working as Masseurs in PERTUNI Community in Semarang - Kusumaningrum, Ervia; Hartati, Elis (Jurnal Keperawatan Soedirman, 2020)
Data show that Central Java ranks 6th for the number of people with disabilities in Indonesia. The Indonesian union for the blind (PERTUNI) community in Semarang reported having 105 people as its members. One of the problems that occur amongst people in PERTUNI is sexual harassment, which results in a negative impact on both their physical and psychological health. This study aimed to identify sexual harassment experiences among visually impaired (blind) adults working as masseurs in the PERTUNI community, Semarang.Â  This research was a qualitative study with a phenomenological approach. The participants were six blind people selected using a purposive sampling technique. The results showed six themes, i.e., helplessness, the fulfillment of daily needs, harassment, the potential for abuse, disruption= of psychological health and avoiding immoral acts. This study concluded that most blind people working as masseurs had experienced sexual harassment in various forms. It is recommended that PERTUNI provides sexual health education as a preventive action to sexual harassment.Â